2020
DOI: 10.7554/elife.60920
|View full text |Cite
|
Sign up to set email alerts
|

Achieving functional neuronal dendrite structure through sequential stochastic growth and retraction

Abstract: Class I ventral posterior dendritic arborisation (c1vpda) proprioceptive sensory neurons respond to contractions in the Drosophila larval body wall during crawling. Their dendritic branches run along the direction of contraction, possibly a functional requirement to maximise membrane curvature during crawling contractions. Although the molecular machinery of dendritic patterning in c1vpda has been extensively studied, the process leading to the precise elaboration of their comb-like shapes remains elusive. Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 123 publications
(178 reference statements)
0
26
0
Order By: Relevance
“…Morphological features of dendritic arbors, such as length, diameter, and orientation have been related to neuronal functions [4][5][6][7][8][9], while deformations of the dendritic architecture have been associated with diseases and disorders [10][11][12][13]. Dendritic morphology varies significantly across species and across neuronal classes, which are often associated with distinct characteristic shapes [1][2][3][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Morphological features of dendritic arbors, such as length, diameter, and orientation have been related to neuronal functions [4][5][6][7][8][9], while deformations of the dendritic architecture have been associated with diseases and disorders [10][11][12][13]. Dendritic morphology varies significantly across species and across neuronal classes, which are often associated with distinct characteristic shapes [1][2][3][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The lateral dendrites of c1da neurons run along the direction of contraction and are sequentially deformed within the consecutive segments during crawling. This branch orientation is thought to maximize membrane curvature during larval crawling and thereby tightly couples c1da dendrite morphology to the neurons' proprioceptive function [12,37]. The four c2da neurons also exhibit a simple dendritic morphology, but with longer branches than c1da neurons.…”
Section: The Da Neurons Of the Drosophila Larvamentioning
confidence: 99%
“…At that stage, da neurons are already polarized and extend their long main dendrites. A recent study investigated the embryonic stages of c1da neuron dendrite differentiation and revealed that the lateral branchlets of c1da neurons underwent repeated cycles of extensive dendritic branch formation and retraction [12]. This process temporarily gave rise to a much higher total number of lateral dendrites, as compared to the final c1da dendritic tree of a third instar larva, and led to the outgrowth of higher-order branches, which in the case of c1da neurons, are never found in the fully developed dendritic tree.…”
Section: Dendrite Differentiation: Noninvasive Long Term In Vivo Imaging Identifies Distinct Phasesmentioning
confidence: 99%
See 2 more Smart Citations